Development and Feasibility Testing of a Multilevel Intervention to Increase Hepatitis C Virus Screening Among Baby Boomers in Primary Care - Monica L. Kasting; Alfu Laily; Lauren D. Nephew; Cleveland G. Shields; Rivienne Shedd-Steele; Susan M. Rawl (Journal of Cancer Education, 2023)
Chronic infection with hepatitis C virus (HCV) results in an increased risk of cirrhosis and hepatocellular carcinoma (HCC). Only 15% of baby boomers (born 1945–1965) have ever been screened. We aimed to develop a multilevel intervention to increase HCV screening for baby boomers in a primary care setting. This study included two phases: intervention development ( phase 1 ) and feasibility testing ( phase 2 ). In phase 1, we partnered with a Community Advisory Board and a Provider Advisory Board to develop a multilevel intervention to increase HCV screening to be delivered to both providers and patients in primary care. Phase 2 assessed intervention feasibility, acceptability, and usability by conducting Concurrent Think Aloud (CTA) interviews and surveys using previously validated scales with patients ( n = 8) and providers ( n = 7). Phase 1 results: The patient-level intervention included a mailed reminder letter and CDC pamphlet and a 7-min in-clinic educational video. The provider-level intervention included a 30-min educational session and monthly performance feedback e-mails. Phase 2 results: Qualitatively, both the patient and provider-level intervention were feasible, acceptable, and usable by the target audiences. Quantitatively, on a 1–4 scale, the range of patient-level scores was 3.00–4.00 and provider level was 3.50–4.00 for feasibility, acceptability, and usability. This intervention could improve HCV screening among a high-risk population and therefore reduce HCV-related morbidity and mortality. This project developed a feasible, acceptable, and usable multilevel intervention aimed at increasing HCV screening in primary care.